Genomics and Molecular Genetics of Plant-Nematode Interactions - Jones, John.; Jones, John.; Gheysen, Godelieve.; Gheysen, Godelieve.; Fenoll, Carmen.; Fenoll, Carmen. (Springer Netherlands : Imprint: Springer, 2011)
Plant parasitic nematodes often establish unique, sophisticated relationships with their hosts, dramatically influencing plant productivity. This book reviews the most recent developments in the molecular biology of plant-nematode interactions that have been driven by the application of genomics tools.  The book will be of interest to postgraduate students and to researchers with an interest in plant nematology and/or plant pathology more generally.  A series of introductory chapters provide a biological context for the detailed reviews of all areas of plant-nematode interactions that follow and ensure that the bulk of the book is accessible to the non-specialist.  Chapters provide not just the exciting state of the art in each field, but also the experts’ views of how they expect that research in each field would develop in the near future. A final section aims to show how these fundamental studies have provided outputs of practical relevance in agriculture.